Museomics reduces taxonomic inflation in the Dendropsophus araguaya complex (Hylinae: Dendropsophini) from the Cerrado - Nakamura, Daniel Y.M.; Orrico, Victor G.D.; Da Silva, Esdras M.G.; Lyra, Mariana L.; Grant, Taran (Journal of Vertebrate Biology, 2025)
The systematics of the Dendropsophus araguaya complex requires a reassessment due to the unknown position of D. rhea, possible misidentifications of D. tritaeniatus, the polyphyly of D. araguaya and D. jimirecovered in a recent total evidence analysis, and intraspecifically variable characters used in diagnoses. We successfully assembled historical DNA from formalin-fixed paratopotype specimens of D. rhea and D. tritaeniatus collected in 1952 and 1963, respectively. Our results revealed that D. rhea is nested within a clade formed by D. cerradensis and D. jimi. Combining evidence from phylogeny, genetic distances, and morphology, we propose that D. jimi and D. rhea are junior synonyms of D. cerradensis. We corroborate the polyphyly of topotypic D. araguaya, with one clade nested within D. cerradensis sensu novo and another that includes a paratopotype of D. tritaeniatus; however, hDNA of the holotype of D. araguaya was not successfully assembled, so we consider D. araguaya to be incertae sedis. We update the name of the D. araguaya complex to the D. cerradensis complex. Furthermore, we also reveal that some specimens previously identified as D. tritaeniatus are D. cachimbo. Our study illustrates the ability of museomics to clarify the taxonomic identity and phylogenetic relationships of possibly extinct species and reduce taxonomic inflation in amphibian systematics.